2022
DOI: 10.1093/beheco/arac073
|View full text |Cite
|
Sign up to set email alerts
|

Kin do not always help: testing multiple hypotheses on nest feeding in a cooperatively breeding bird

Abstract: In cooperatively breeding species, group members may derive multiple benefits from helping to raise other individuals’ offspring, yet not all individuals do so. In this study, we tested predictions from the “kin selection”, “pay-to-stay”, “group augmentation” and “skills” hypotheses, to explain why group members feed nestlings of breeding placid greenbuls (Phyllastrephus placidus). In our study population, about 70% of the breeding pairs were accompanied by subordinates, and in 60% of these cases at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…We have previously shown that cooperatively breeding males and females have higher annual survival than pair breeders. 40 Whether these fitness benefits are retained in low quality territories remains to be tested, but the present results suggest that through reduced physiological costs, as evidenced by low baseline corticosterone levels, breeders from cooperative groups may be able to avoid the survival costs of breeding in small fragments. 48 …”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…We have previously shown that cooperatively breeding males and females have higher annual survival than pair breeders. 40 Whether these fitness benefits are retained in low quality territories remains to be tested, but the present results suggest that through reduced physiological costs, as evidenced by low baseline corticosterone levels, breeders from cooperative groups may be able to avoid the survival costs of breeding in small fragments. 48 …”
Section: Discussionmentioning
confidence: 73%
“…In placid greenbuls and other cooperative species, subordinates commonly contribute less to nestling provisioning than the breeding pair. 40 , 49 Lower baseline corticosterone levels in subordinates than breeders indicate that they can keep the physiological costs of helping low. 47 Although some subordinates do not provide any help 40 and therefore may have low corticosterone levels, because subordinates were caught at the nest, it is likely that they were indeed helping to feed the offspring of the breeding pair.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations